2002
DOI: 10.1074/jbc.m108789200
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Stimulates Phosphorylation of Endothelial Nitric-oxide Synthase at Ser1179 by Akt-independent Mechanisms

Abstract: 1179 in a PKA-dependent, but Aktindependent manner, whereas the NO ⅐ production is regulated by the mechanisms dependent on both PKA and Akt. A coordinated interaction between Akt and PKA may be an important mechanism by which eNOS activity is regulated in response to physiological stimuli such as shear stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
312
7
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(352 citation statements)
references
References 42 publications
25
312
7
7
Order By: Relevance
“…However, several lines of evidence have shown that PKA also regulates the phosphorylation of eNOS at Ser 1179 , Ser 635 , and Ser 617 in bovine eNOS (Ser 1177 , Ser 633 , and Ser 615 in humans) [24,[26][27][28][29] . Ser 633/635 phosphorylation is critical in maintaining NO synthesis after the initial sensitization by Ca 2+ flux and Ser 1177/1179 phosphorylation [30] , and it is stimulated via the PKA pathway in response to shear stress and acute statin treatment in aortic endothelial cells [24,27] , suggesting that PKA-mediated Ser 633/635 phosphorylation may be another mechanism by which statins protect against myocardial no-reflow and necrosis after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, several lines of evidence have shown that PKA also regulates the phosphorylation of eNOS at Ser 1179 , Ser 635 , and Ser 617 in bovine eNOS (Ser 1177 , Ser 633 , and Ser 615 in humans) [24,[26][27][28][29] . Ser 633/635 phosphorylation is critical in maintaining NO synthesis after the initial sensitization by Ca 2+ flux and Ser 1177/1179 phosphorylation [30] , and it is stimulated via the PKA pathway in response to shear stress and acute statin treatment in aortic endothelial cells [24,27] , suggesting that PKA-mediated Ser 633/635 phosphorylation may be another mechanism by which statins protect against myocardial no-reflow and necrosis after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated eNOS activity observed in rodents with elevated EPO levels has been attributed to increased shear stress created by the increase in hematocrit, since shear stress can stimulate eNOS activity by a variety of mechanisms including increasing eNOS mRNA expression and/or stability, or eNOS protein phosphorylation. 42,43 However, in patients with polycythemia-who are not receiving exogenous EPO (and who may have very low EPO levels)-high hematocrit appears to inhibit endothelium-dependent vasodilatation in response to acetylcholine. This process can be reversed by hemodilution and normalization of blood hemoglobin concentration.…”
Section: Org Frommentioning
confidence: 99%
“…Bovine aorta endothelial cells (BAECs) harvested from descending thoracic aortas were maintained (37 o C, 5% CO2) in a growth medium [Dulbecco's modified Eagle's medium (DMEM) containing 1 g/l glucose (Gibco) and 20% fetal bovine serum (FBS, Atlanta Biologicals) without antibiotics] (Boo et al, 2002b). BAECs used in this study were between passages 5 and 10.…”
Section: Cell Culture and Shear Stress Treatmentsmentioning
confidence: 99%
“…The recombinant adenoviral construct, Ad-Akt-Myr, was used to express a constitutively active Akt mutants generated by fusing a myristoylation signal to its amino terminus Boo et al, 2002b). Recombinant adenovirus encodinggalactosidase (Ad--gal) was used as a control.…”
Section: Adenoviral Infectionmentioning
confidence: 99%